Sustainable Business Practices and Corporate Financial Performance: A Panel Data Analysis - Shinde Suvarna (International Journal of Economic and Business Research, 2026)
This study examines the relationship between sustainable business practices and corporate financial performance using panel data from firms across multiple sectors and regions. Sustainability is conceptualized through environmental, social, and governance (ESG) dimensions, while financial performance is measured using accounting-based and market-based indicators. The analysis identifies that firms with higher sustainability performance achieve improved operational efficiency, risk mitigation, capital market access, and long-term strategic resilience. Moderating factors such as governance quality, stakeholder engagement, sectoral characteristics, and institutional frameworks influence the strength and persistence of these effects. Panel regression techniques, including fixed-effects and random-effects models, reveal dynamic and heterogeneous patterns in the sustainability–financial performance relationship, highlighting both immediate and lagged effects. Empirical evidence across global, emerging, and sector-specific contexts underscores that sustainable practices serve as strategic investments rather than cost burdens. The findings provide actionable insights for managers, policymakers, and investors seeking to leverage sustainability initiatives to enhance long-term profitability and firm value while promoting responsible corporate behavior.